Prosedur Administrasi Pelayanan Pemakaman Pada TPU Tegal Alur Unit II Islam Jakarta Barat - Akhmad Nurdiansyah; Ria Andriani; Dwi Puji Hastuti (Universitas Bina Sarana Informatika, 2019)
The place funeral general which serves as a burial place for people who died. Funeral general also has other functions such as the Green Open Space, catchment area water, and lungs of the city. The author uses descriptive qualitative research methods. Sources of data in this study were obtained using the data used, interviews and documentation TPU Tegal Alur Unit II Islam which located in Jl.Kamal Raya No.1A. Kelurahan Tegal Alur. Kecamatan Kalideres. Kota Administrasi Jakarta Barat 11820. As well as interviews with that related source. The place funeral general tegal alur is a public cemetery that stands from the wakaf land owned by local residents. At the tomb was previously there is a tomb of Muslims and non-Muslims. TPU Tegal Alur Unit II Islam other than moving in service funeral, as providing information on funerals and retribution rates in general. TPU Tegal Alur Unit II Islam also one of the manufacturers for finance area ie within retribution service funeral.Keywords: Procedure, Administration, Service